Розробка інтегрованої моделі екологічно безпечної утилізації фосфогіпсу в технологіях захисту навколишнього середовища - Черниш, Єлизавета Юріївна (НТУ "ХПІ", 2017)
У роботі була здійснена формалізація методологічного підходу щодо процесу формування концепції поводження з фосфогіпсом на принципах екологічної безпеки. Сформовано інтегровану модель екологічно безпечної утилізації фосфогіпсу в технологіях захисту навколишнього середовища, за допомогою якої можливо здійснити детермінацію взаємозв'язків в суміжних сферах використання мінеральних носіїв на основі фосфогіпсу з інтеграцією окремих технологічних рішень в системі захисту водних екосистем, атмосферного повітря та процесів відновлення забруднених ґрунтів та розроблено модель оцінювання ефективності використання фосфогіпсу в технологіях очищення компонентів середовища за рядом еколого-біохімічних показників.

This paper focused on the development of scientific and theoretical foundations for conducting research on the environmentally safe disposal of phosphogypsum in environmental protection technologies. The biochemical direction of technological solutions for the phosphogypsum treatment as a mineral raw material to stimulate the development of the necessary ecological trophic groups of microorganisms is developed. The methodological approach was formalized in the ecologicalsynergetic concept of phosphogypsum wastes using. At the same time, paper focused on the interconnection in related spheres of the use of mineral carriers based on phosphogypsum with the integration of individual technological solutions in the system of protection of aquatic ecosystems, atmospheric air and the processes of restoring contaminated soils. The biochemical conversion will be able to provide efficient purification of environmental components using phosphogypsum and products of its processing as supply medium in biotechnological environmental protection systems. In the process of phosphogypsum conversion, a mineral carrier is obtained for the immobilization of microorganisms in the technologies of aquatic ecosystems protection, biochemical gas purification from sulfur compounds, in remediation processes of contaminated soils. The scheme for the determination of ecologomicrobiological parameters was developed for estimation of the effectiveness of using phosphogypsum as a mineral substrate by different groups of microorganisms in environmental protection technologies.
Development of the integrated model of ecologically safe utilization of phosphogypsum in environmental protection technologies
Keywords: формалізація; безпека екологічна; переробка відходів; технології біохімічні; integrated model; phosphogypsum; environmental protection; formalization; ecological safety